Analysis of Golgi complex functions: in vitro reconstitution systems - Adolf, Frank; Wieland, Felix T. (Methods for analysis of Golgi complex function, 2013)
In vitro reconstitution is prerequisite to investigate complex cellular functions at the molecular level. Reconstitution systems range from combining complete cellular cytosol with organelle-enriched membrane fractions to liposomal systems where all components are chemically defined and can be chosen at will. Here, we describe the in vitro reconstitution of COPI-coated vesicles from semi-intact cells. Efficient vesicle formation is achieved by simple incubation of permeabilized cells with the minimal set of coat proteins Arf1 and coatomer, and guanosine trinucleotides. GTP hydrolysis or any mechanical manipulations are not required for efficient COPI vesicle release.
Gesehen am 06.05.2021